D-Cateslytin, a new antimicrobial peptide with therapeutic potential. Issue 1 (December 2017) - Zaet, Abdurraouf; Dartevelle, Pauline; Daouad, Fadoua; Ehlinger, Claire; Quilès, Fabienne; Francius, Grégory; Boehler, Christian; Bergthold, Camille; Frisch, Benoît; Prévost, Gilles; Lavalle, Philippe; Schneider, Francis; et al.
Abstract The rise of antimicrobial resistant microorganisms constitutes an increasingly serious threat to global public health. As a consequence, the efficacy of conventional antimicrobials is rapidly declining, threatening the ability of healthcare professionals to cure common infections. Over the last two decades host defense peptides have been identified as an attractive source of new antimicrobials. In the present study, we characterized the antibacterial and mechanistic properties of D-Cateslytin (D-Ctl), a new epipeptide derived from L-Cateslytin, where all L-amino acids were replaced by D-amino acids. We demonstrated that D-Ctl emerges as a potent, safe and robust peptide antimicrobial with undetectable susceptibility to resistance. Using Escherichia coli as a model, we reveal that D-Ctl targets the bacterial cell wall leading to the permeabilization of the membrane and the death of the bacteria. Overall, D-Ctl offers many assets that make it an attractive candidate for the biopharmaceutical development of new antimicrobials either as a single therapy or as a combination therapy as D-Ctl also has the remarkable property to potentiate several antimicrobials of reference such as cefotaxime, amoxicillin and methicillin.